Methods to Study Centrosomes and Cilia in Drosophila - Jana, Swadhin Chandra (2018)
The deposited item is a book chapter and is part of the series " Methods in Molecular Biology book series ([MIMB, volume 1454]) published by the publisher Humana Press.